Translational repression of the cpw-wpc gene family in the malaria parasite Plasmodium - Rao, Pavitra N.; Mair, Gunnar R. (Parasitology international, 2016)
The technical challenges of working with the sexual stages of the malaria parasite Plasmodium have hindered the characterization of sexual stage antigens in the quest for a successful malaria transmission-blocking vaccine. One such predicted and largely uncharacterized group of sexual stage candidate antigens is the CPW-WPC family of proteins. CPW-WPC proteins are named for a characteristic domain that contains two conserved motifs, CPxxW and WPC. Conserved across Apicomplexa, this family is also present earlier in the Alveolata in the free-living, non-parasitophorous, photosynthetic chromerids, Chromera and Vitrella. In Plasmodium falciparum and Plasmodium berghei blood stage parasites, the transcripts of all nine cpw-wpc genes have been detected in gametocytes. RNA immunoprecipitation followed by reverse transcriptase-PCR reveals all P. berghei cpw-wpc transcripts to be bound by the translational repressors DOZI and CITH, and thus are likely under translational control prior to transmission from the rodent host to the mosquito vector in P. berghei. The GFP tagging of two endogenous P. berghei genes confirmed translational silencing in the gametocyte and translation in ookinetes. By establishing a luciferase transgene assay, we show that the 3′ untranslated region of PF3D7_1331400 controls protein expression of this reporter in P. falciparum gametocytes. Our analyses suggest that cpw-wpc genes are translationally silenced in gametocytes across Plasmodium spp. and activated during ookinete formation and thus may have a role in transmission to the mosquito.
Gesehen am 26.01.2021